Left intraventricular dyssynchrony caused by a false tendon. Issue 3 (23rd October 2014) - Irie, Tadanobu; Kurosawa, Koji; Kaneko, Yoshiaki; Nakajima, Tadashi; Tateno, Rieko; Kurabayashi, Masahiko
Abstract: Left ventricular (LV) false tendons are usually benign, intraventricular myocardial structures, which may cause functional malfunction or deformation of the LV cavity due to mechanical stretching and dilatation of the LV wall. We present a case of non‐ischemic cardiomyopathy complicated with intraventricular dyssynchrony that was caused by complete left bundle branch block and the mechanical pressure exerted by the stiff false tendon on the weakened mid‐septum during systole.